Alexander Dumas's The three Musketeers - Stahlberg, Lance (Stone Arch Books, a Capstone imprint, 2017)
A graphic novel adaptation of Alexandre Dumas's classic tale about a young Frenchman, D'Artagnan, who travels to Paris in order to join the King's elite fighting force and comes under the influence of three of the Musketeers, Athos, Porthos, and Aramis.